2021
DOI: 10.1002/jso.26373
|View full text |Cite
|
Sign up to set email alerts
|

Is resection for noncolorectal, nonneuroendocrine liver metastases justified?

Abstract: Introduction The role of hepatectomy in non‐colorectal, nonneuroendocrine liver metastasis (NCNN) is not clearly defined. This study represents a step towards surgical frame‐shift as an integral part of treatment pathway in these heterogeneous, arbitrarily treated tumors. It aims to provide answers regarding favorable tumor types and patient profiles for which liver metastasectomy would prove beneficial. Materials and Methods Retrospective analysis of prospectively maintained database of hepatectomy in NCNN li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Thus, we were not able to identify any factors that significantly impaired overall survival following surgery on NCRNNELM. This finding was in line with the recent publications of Patkar et al and Lok et al with similar sample sizes [ 37 , 38 ]. This suggested that patients with NCRNNELM could benefit from radical treatment in the long run.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, we were not able to identify any factors that significantly impaired overall survival following surgery on NCRNNELM. This finding was in line with the recent publications of Patkar et al and Lok et al with similar sample sizes [ 37 , 38 ]. This suggested that patients with NCRNNELM could benefit from radical treatment in the long run.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have reported favorable outcomes in patients with breast cancer who underwent resection of brain [ 12 , 13 ] and bone metastases [ 14 ]. Hence, surgical resection may be a promising treatment option in cases of breast cancer with liver metastases (BCLM) [ 15 ]. Recent studies have demonstrated that liver resection can improve survival beyond 5 or 10 years after BCLM surgery [ 16 19 ].…”
Section: Introductionmentioning
confidence: 99%